2021
DOI: 10.1002/solr.202100151
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Induced Degradation of Cathode Interface Layer in PM7:IT‐4F Polymer Solar Cells

Abstract: Cathode buffer layer interface modification is a commonly used strategy to prepare high‐efficient organic solar cells (OSCs). Nonfullerene OSCs based on PM7:IT‐4F are prepared and modified with poly[(9,9‐bis(3′‐(N,N‐dimethylamino)propyl)‐2,7‐fluorene)‐alt‐2,7‐(9,9‐dioctylfluorene)] (PFN)‐Br cathode buffer layer. The introduction of the PFN‐Br buffer layer obviously boosts the photovoltaic performance of PM7:IT‐4F‐based OSCs, however, the stability of the PFN‐Br‐modified device shows a serious degradation. By e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…With the expectation of compromising the effect of the two kinds of additives, binary additives have been investigated in the past few years. [124][125][126][127][128][129] For instance, He and Zhao et al reported the OSC based on FTAZ:IDCIC (Fig. 2) with the binary additive, 1-CN&DIO, afforded a decent PCE of 13.58%, much higher than the counterparts with no additive (9.64%), DIO (9.76%), and CN (11.81%), respectively.…”
Section: Binary Additivesmentioning
confidence: 99%
“…With the expectation of compromising the effect of the two kinds of additives, binary additives have been investigated in the past few years. [124][125][126][127][128][129] For instance, He and Zhao et al reported the OSC based on FTAZ:IDCIC (Fig. 2) with the binary additive, 1-CN&DIO, afforded a decent PCE of 13.58%, much higher than the counterparts with no additive (9.64%), DIO (9.76%), and CN (11.81%), respectively.…”
Section: Binary Additivesmentioning
confidence: 99%
“…As a result, charge transport and extraction are hindered, leading to a degraded device performance. [ 66 ] So far, there needs to be more research on the electrical effect on the stability of high‐efficiency OSCs and its mechanism.…”
Section: Factors Limiting the Stability Of Oscsmentioning
confidence: 99%
“…Previous studies show that PFN-Br-modified OPVs exhibit photovoltaic performance degradation attributed to an increase in the interface resistance caused by the deterioration of the cathode buffer layer (PFN-Br). [32,33] The deterioration is enhanced by the strong polar group in PFN-Br structure. Because the N-annulated PDI does not have a strong polar group in its structure, this degradation mechanism is minimized with PDIN-EH, which leads to a superior charge transport and charge extraction at the interface between the active layer and electrode.…”
Section: Device Stabilitymentioning
confidence: 99%